Challenges of Scientific Research in Palestinian Universities and Avenues for its Enhancement: Perspectives of Ph.D. Students in West Bank Universities - Matar, Osama Issam; Jawabreh, Reem Mashhour; Radwan, Haya Yaser; Gharabeh, Thaher Mohamed; Kaleef, Sherin Wael; Ayyash, Mohammad Shareef; Abu Shomer, Diya Mohammed; Alhajhamad, Abedelrahman Aqel; Halabi, Aseel Adly; Abualrob, Ashraf Mohammed (Journal of Educational and Psychological Sciences, 2023)
The current study aimed to identify the status quo of Palestinian scientific research between reality and hope from the point of view of Ph.D. students, and the researchers adopted a descriptive methodology. The researchers prepared a questionnaire consisting of 21 items as a study tool for data collection, and it was distributed to a random sample of (51) male and female researchers. The results showed the majority of challenges were related to the lack of scientific research funding, where her proportion was very significant, reaching 88%; the lack of training opportunities for scientific research outside the framework of universities, reaching 65%, and the lack of ability and knowledge of scientific research and publishing strategies, reaching 33%. The study recommends increasing funding, strengthening the research infrastructure, including developing research institutions, and improving access to scientific databases, literature, and all other scientific sources that a researcher needs.